2016
DOI: 10.2147/dddt.s111253
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine improves left ventricle diastolic function in streptozotocin-induced diabetic mice

Abstract: Diabetes is a potent risk factor for heart failure with preserved ejection fraction (HFpEF). Autophagy can be activated under pathological conditions, including diabetic cardiomyopathy. The therapeutic effects of chloroquine (CQ), an autophagy inhibitor, on left ventricle function in streptozotocin (STZ)-induced diabetic mice were investigated. The cardiac function, light chain 3 (LC3)-II/LC3-I ratio, p62, beclin 1, reactive oxygen species, apoptosis, and fibrosis were measured 14 days after CQ (ip 60 mg/kg/d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…These pathological changes cause cardiac stiffness and consequent left ventricular diastole (Murtaza et al, 2019). The present study validated our earlier finding (Yuan et al, 2016) that diabetes leads to cardiac remodeling and diastolic dysfunction in both mice with T1DM and T2DM; this finding was supported by the increased gene expression of cardiac hypertrophic markers ( Nppa and Myh7 ), aggravation of cardiac fibrosis, and decreased E/A ratio in both types of diabetic mice. Furthermore, these changes indicate that mice with T1DM and T2DM had DCM, which significantly improved on carvacrol treatment.…”
Section: Discussionsupporting
confidence: 92%
“…These pathological changes cause cardiac stiffness and consequent left ventricular diastole (Murtaza et al, 2019). The present study validated our earlier finding (Yuan et al, 2016) that diabetes leads to cardiac remodeling and diastolic dysfunction in both mice with T1DM and T2DM; this finding was supported by the increased gene expression of cardiac hypertrophic markers ( Nppa and Myh7 ), aggravation of cardiac fibrosis, and decreased E/A ratio in both types of diabetic mice. Furthermore, these changes indicate that mice with T1DM and T2DM had DCM, which significantly improved on carvacrol treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Echocardiography was done using Visualsonic Ultrasound System (Vevo770, Toronto, Canada) containing a 40 Mhz variable frequency probe. Standard imaging planes, M-mode, color-mode, Doppler, PW Doppler mode views were recorded when the mouse possessed a target heart rate between 450 and 550 beats per minute ( 44 ). Functional calculations were acquired according to the guidelines of the American Society of Echocardiography.…”
Section: Methodsmentioning
confidence: 99%
“…In hypertrophic heart, autophagic processes are activated and studies on Beclin-1 suggested that autophagy enhanced tissue remodeling and disease progression [9,10]. In line with these results, treatment with autophagy inhibitor chloroquine ameliorated diastolic function and cardiac fibrosis in diabetic mice [11]. On the other hand, genetic deficiency of autophagy effector protein Atg5 led to increased hypertrophy and cardiac fibrosis [8,12].…”
Section: Introductionmentioning
confidence: 79%
“…Here, we demonstrated a novel mechanism, by which the TGF-ÎČ-Fosl-2 axis regulated profibrotic changes in cardiac fibroblasts by activating autophagocytosis. Previous studies have already shown the significance of autophagy in promoting fibrotic processes in multiple organs including skin [ 25 ], lung [ 26 ], liver [ 27 ], kidney [ 28 ] and heart [ 9 , 10 , 11 ]. It should be noted that in the heart, autophagocytosis might also be involved in antifibrotic and cardioprotective processes [ 8 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%